Accurate BER analysis of downlink DS/CDMA multicellular systems in Nakagami fading - Pongsatorn Sedtheetorn (2018)
This paper presents an accurate analysis of bit error rate for a downlink DS/CDMA multicellular system in Additive White Gaussian Noise (AWGN) Nakagami fading channel. Based on Improved Gaussian Approximation (IGA) technique, we propose an exact bit error rate expression. In addition, for a special case of Nakagami fading when the fading index becomes unity, we extend the analysis to include the effect of intracell interference, which is the consequence of losing orthogonality among the transmissions within the same cell. This facilitates us to introduce an explicit closed-form expression of the error rate that accounts for both intracell as well as intercell interferences. The proposed expressions are very useful for accurately investigating the impacts of orthogonality, propagational condition and severity of fading level on bit error rate.